Risk-based regulation and supervision of second-tier banks: experience of EU countries - Alina, Gulzhan; Zhurakhovska, Liudmyla; Dugalova, Gulnar; Utegenova, Zhuldyz; Omarova, Balnur; Murzatayev, Yerzhan (Business: Theory and Practice, 2024)
The aim of the study was to determine the impact of increased capital adequacy standards of second-tier banks on their performance. The study is based on second-tier banks of EU member states, as these countries are the first to implement the Basel Committee recommendations, so their experience should be studied and taken into account when building risk-based regulation of second-tier banks of Ukraine and Kazakhstan. The study covers the period of 2009–2022, as the Basel III regulations were adopted after 2008, and they began to operate for the second-tier banks of EU member states in 2013. The study was conducted using econometric modelling with an analysis of the dependence of banking indicators on the capital structure established by Basel III. Functional interrelationships of the dependence of Net Interest Income, Profit, Return on Assets, Return on Equity, Risk Costs to Operating Income were tested. The impact of capital adequacy requirements on the performance of second-tier banks was determined: capital adequacy requirements have a positive impact on net interest income and profit of second-tier banks. The obtained results can be used to substantiate increasing capital adequacy requirements to increase the reliability of the banking system as an element in the system of factors of economic growth of the national economy.